Role of Auditor Independence in Enhancing Audit Quality: Evidence from Nigeria’s Insurance Sector - Timothy Aondona Aondover (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2025)
This study examines the role of auditor independence in enhancing audit quality, with a focus on listed insurance companies in Nigeria. Auditor independence is a cornerstone of credible financial reporting, and its influence on audit quality remains a critical area of interest, particularly in sectors such as insurance that are highly regulated and sensitive to public trust. The paper adopts secondary data based on the available existing studies in the area. Key indicators of auditor independence, such as audit firm tenure, provision of non-audit services, audit fees, and regulatory compliance, are assessed against established measures of audit quality, including financial report accuracy, detection of material misstatements, and stakeholder confidence. The paper argues that there a significant positive correlation between auditor independence and audit quality, underscoring the importance of strict adherence to ethical standards and regulatory frameworks. The study affirms that auditor independence plays a critical role in enhancing audit quality within Nigeria’s insurance sector. Independent auditors are better positioned to deliver objective, unbiased assessments of financial statements, thereby strengthening the credibility and reliability of financial reporting. The findings reveal that key elements such as audit firm tenure, non-audit service restrictions, and regulatory oversight significantly influence the degree of auditor independence and, by extension, the quality of audits conducted. Despite the progress made, challenges such as long auditor-client relationships, inadequate enforcement of auditor rotation, and the provision of non-audit services continue to undermine audit objectivity in the sector.